Effects of N-Acetylcysteine on fatigue, critical power, and muscle energy stores - Corn, Sarah D. (Kansas State University, 2009)
The accumulation of reactive oxygen species (ROS) has been linked to the development of muscular fatigue. Antioxidant administration has the potential to counteract the increased levels of ROS, leading to improvements in performance. N-acetylcysteine (NAC), a nonspecific antioxidant, is especially promising due to its ability to support the biosynthesis of glutathione, one of the primary endogenous antioxidants. Despite this, the effects of NAC on time to fatigue appear to be dependent upon the exercise intensity, with the more pronounced effects evident at submaximal exercise intensities. The purpose of this study was to determine the effects of an acute dose of NAC on whole body fatigue, critical power (CP) and W’ during high-intensity exercise. It was hypothesized that pretreatment with NAC would result in (1) an increase in time to fatigue (TTF), CP and W’, (2) NAC administration would attenuate changes in the EMG responses indicative of fatigue, and (3) speeding of the kinetics of the primary phase of VO2 and a reduction in the slow component. Seven healthy, active males (age: 21.4 ± 1.6 years, weight: 89.1 ± 11.0 kg, height: 183 ± 5 cm) completed an incremental ramp test until exhaustion for the determination of peak VO2 and power. Four tests were subsequently performed at power outputs corresponding to 80, 90, 100, and 110% Pmax under NAC and placebo (PLA) conditions. NAC resulted in a significant increase in [tGSH] in red blood cells compared to baseline and PLA condition. TTF was significantly increased only in the 80% Pmax trial (p = 0.033). CP was also significantly higher with NAC (NAC: 232 ± 28 W vs PLA: 226 ± 31 W; p = 0.032), but W’ showed a tendency to decrease (NAC: 15.5 ± 3.8 kJ vs W’: 16.4 ± 4.5 kJ). The change in W’ was negatively related to CP (r = -0.96), indicating that the increase in CP was associated with a decrease in W’. EMG analysis revealed a tendency for MdPF and RMS to demonstrate less of a change with NAC. There were no significant differences in VO2 kinetics, but an inverse relationship was observed between the change in τp and the magnitude of the slow component expressed both in absolute terms (r = -0.632, p = 0.007) and as a gain (r = -0.751, p = 0.0005). We conclude that NAC was effective in delaying fatigue and improving exercise performance at 80% peak power, although the exact mechanisms are still unclear.
Keywords: N-Acetylcysteine; critical power; W'; electromyography; oxygen uptake kinetics; Health Sciences, General (0566)